2019
DOI: 10.15406/ppij.2019.07.00240
|View full text |Cite
|
Sign up to set email alerts
|

The resistance growing trend of common gramnegative bacteria to the potential antibiotics over three consecutive years: a single center experience in Bangladesh

Abstract: The increasing trend of antibiotic resistance is a global emergence. The susceptibility of the most common gram-negative bacteria (GNB) are reducing day-by-day to potential antibiotics as a result of different enzymatic and non-enzymatic resistancemechanisms of bacteria and disseminating the resistance-gene throughout the intra and inter-bacterial communities rapidly. The objective of this study was to evaluate the resistance developing trends of common GNB against the potential antibiotics over three consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…More than 80% of MRSA isolates are also found to be sensitive to some macrolides (tobramycin, gentamycin) and carbapenem (meropenem) with resistant to ampicillin, amoxicillin, cefixime and azithromycin [46]. Antibiogram from a private sector tertiary hospital over three years (2016)(2017)(2018) shows that the last resort antimicrobials (Polymyxin B and Colistin) retained their high sensitivity to Klebsiella, Psudomonos, and E. coli [47]. A review by GARP-Bangladesh National Working Group provided a descriptive analysis of the AMR situation in different sectors along with recommendations [48].…”
Section: A1ntimicrobialmentioning
confidence: 99%
“…More than 80% of MRSA isolates are also found to be sensitive to some macrolides (tobramycin, gentamycin) and carbapenem (meropenem) with resistant to ampicillin, amoxicillin, cefixime and azithromycin [46]. Antibiogram from a private sector tertiary hospital over three years (2016)(2017)(2018) shows that the last resort antimicrobials (Polymyxin B and Colistin) retained their high sensitivity to Klebsiella, Psudomonos, and E. coli [47]. A review by GARP-Bangladesh National Working Group provided a descriptive analysis of the AMR situation in different sectors along with recommendations [48].…”
Section: A1ntimicrobialmentioning
confidence: 99%
“…pneumoniae toward colistin. [ 20 ] One systematic review in Bangladesh reported 18.8% median resistance to colistin which ranged from 0% to 21.4%. [ 19 ] It may be due to the increased use of these drugs in clinical settings coupled with the horizontal transfer of genetic elements including resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance is widespread, and resistance among Gram-negative critical pathogens have reached alarming levels, and inappropriate antibiotic use has been identified as a major contributor to this phenomenon (Hasan et al, 2019). Bacteria evolved resistance against the antibacterial agents as et al, 2013).…”
Section: Introductionmentioning
confidence: 99%